Jonas Biliūnas’ Materialistic Views - Barzdaitis, Juozas (Problemos, 1978)
The literary heritage of Jonas Biliūnas, a Lithuanian writer – democrat, a social and cultural figure, is rich in works revealing the author’s philosophical views. In the article J. Biliūnas’ materialistic world outlook is discussed. It was in a materialist way that he solved the principal problem of philosophy, elements of dialectics being characteristic of his views. He was an opponent of agnosticism and a follower of materialistic theory of knowledge. At the same time he tried to overcome the limited character of pre-Marxist materialism.